PSYCHOLOGICAL ASPECTS OF THE PHENOMENON OF PATRIOTISM (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article analyzes the phenomenon of patriotism from a psychological point of view and explains that it consists of several structural components. As the main structural components, such characteristics as love for the Motherland, involvement in the future of one's country, correct identification with the history and values of one's country, and spreading the glory of the Motherland to the world are analyzed.